Genotypic and phenotypic characterization of food-associated Lactobacillus plantarum isolates for potential probiotic activities. Issue 10 (9th May 2020) - Prete, Roberta; Long, Sarah L; Joyce, Susan A; Corsetti, Aldo
ABSTRACT: Lactic acid bacterium, Lactobacillus plantarum, has been applied, for centuries, for food and drink fermentations. Given the benefits associated with fermented products, Lb. plantarum strains have captured considerable industrial and scientific interest, so that they are included as fundamental components of functional foods. Indeed, some strains are marketed as probiotics. In the present study, food- and gut-associated Lb. plantarum isolates were genetically characterized by multilocus sequence typing (MLST) and phenotypically characterized for properties that could influence their probiotic potential. MLST and phylogenetic analysis stratified 22 Lb. plantarum isolates into six lineages. The isolates were further phenotypically characterized by an in vitro assay to assess their potential gut community influence via a limited number of assays including acidification activity, strain displacement activity and their intrinsic range of antibiotic resistance. Given growing recognition of the benefits of fermented foods, and the prevalence of Lb. plantarum in these applications, this study highlights analysis of a subset of preliminary important strain-specific features. These features are of interest to all stakeholders, to inform isolate comparison and selection for current functional food associations, and that can serve as a basis for future strain and food-microbe fermentation product development. Abstract : This study supports a specific preliminary platform to characterize Lactobacillus plantarum intended for fermentation purposes and for probiotic consumption on the basis of genotype and phenotype.